The Effect of Sleep Deprivation on Cardiac Function and Tolerance to Ischemia-Reperfusion Injury in Male Rats - Jeddi,Sajad (2016)
Abstract Background: Sleep deprivation (SD) is strongly associated with elevated risk for cardiovascular disease. Objective: To determine the effect of SD on basal hemodynamic functions and tolerance to myocardial ischemia-reperfusion (IR) injury in male rats. Method: SD was induced by using the flowerpot method for 4 days. Isolated hearts were perfused with Langendorff setup, and the following parameters were measured at baseline and after IR: left ventricular developed pressure (LVDP); heart rate (HR); and the maximum rate of increase and decrease of left ventricular pressure (±dp/dt). Heart NOx level, infarct size and coronary flow CK-MB and LDH were measured after IR. Systolic blood pressure (SBP) was measured at start and end of study. Results: In the SD group, the baseline levels of LVDP (19%), +dp/dt (18%), and -dp/dt (21%) were significantly (p < 0.05) lower, and HR (32%) was significantly higher compared to the controls. After ischemia, hearts from SD group displayed a significant increase in HR together with a low hemodynamic function recovery compared to the controls. In the SD group, NOx level in heart, coronary flow CK-MB and LDH and infarct size significantly increased after IR; also SD rats had higher SBP after 4 days. Conclusion: Hearts from SD rats had lower basal cardiac function and less tolerance to IR injury, which may be linked to an increase in NO production following IR.